Challenges and opportunities in integrating electric vehicles with distributed renewable generation - Mahammad Anwar; Abdul Khadar Asundi; Shabana Sultan Sarmas (Institute of Advanced Engineering and Science, 2026)
Electric vehicles (EVs) and distributed generation (DG) based on renewable energy sources (RES), mainly solar photovoltaics (PV) and wind, are the two main pillars of the current smart grid. EVs are growing in popularity. They promise improved resilience and sustainability through their synergistic combination. This review essay offers a thorough analysis of the opportunities and difficulties present in this pairing. We examine that managing the dual intermittency of renewable energy and EV mobility puts pressure on grid stability and power quality. This study carefully compares the performance, economic feasibility, and grid implications of several integration architectures, ranging from hybrid systems and vehicle-to-grid (V2G) ecosystems to solar and wind-powered charging stations. This work also analyzes the important trade-offs between grid hosting capacity (HC), cost vs reliability, and infrastructure centralization. According to the study, the main socioeconomic and technical obstacles to scalability are antiquated regulations, battery degradation issues, and a lack of standardized interoperability. To turn EVs from a grid burden into a versatile asset for a decarbonized energy future, the study concludes by outlining critical future research topics, highlighting the necessity of AI-driven energy management systems (EMSs), sophisticated vehicle-to-everything (V2X) services, and dynamic HC analysis.